2007
DOI: 10.1002/ps.1353
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of herbicides on plants and algae: do species and test systems matter?

Abstract: Risk assessment of herbicides towards non-target plants in Europe is currently based solely on tests on algae and floating aquatic plants of Lemna sp. Effects on terrestrial non-target species is not systematically addressed. The purpose of the present study was to compare combination effects of herbicide mixtures across aquatic and terrestrial test systems, and to test whether results obtained in the traditional aquatic test systems can be extrapolated to the terrestrial environment. This was done by evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 37 publications
4
54
1
3
Order By: Relevance
“…Contrary to our findings, antagonism was the most common type of interaction found in the study of Cedergreen et al (2007b), where effects of herbicide mixtures on aquatic and terrestrial test systems were assessed. In this study the authors found asymmetric isoboles for the mixture of terbuthylazine and diquat on the terrestrial plant Stellaria media, suggesting that only a small amount of terbuthylazine would reduce the effect of diquat dramatically, whereas small amounts of diquat would have only a small effect on the efficacy of terbuthylazine (Cedergreen et al 2007b).…”
Section: Binary Mixture Toxicity Testscontrasting
confidence: 84%
“…Contrary to our findings, antagonism was the most common type of interaction found in the study of Cedergreen et al (2007b), where effects of herbicide mixtures on aquatic and terrestrial test systems were assessed. In this study the authors found asymmetric isoboles for the mixture of terbuthylazine and diquat on the terrestrial plant Stellaria media, suggesting that only a small amount of terbuthylazine would reduce the effect of diquat dramatically, whereas small amounts of diquat would have only a small effect on the efficacy of terbuthylazine (Cedergreen et al 2007b).…”
Section: Binary Mixture Toxicity Testscontrasting
confidence: 84%
“…1a, Table 3). The EC 50 of metsulfuron in this experiment was, however, rather high compared to previous experiments (Table 2) (Cedergreen et al 2007b). A repetition of the experiment could not reproduce the synergy but showed no deviation from either of the reference models (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…It was therefore possible to make mixture ratio experiments with malathion resulting in dose-response surfaces (Greco et al 1995). This was done according to Cedergreen et al (2007b) using mixture ratios chosen to give a division of effect between the herbicide and the insecticide of 100:0, 83:17, 63:37, 50:50, 37:63, 17:83, 0:100% based on EC 50 values from previous experiments.…”
Section: Combination Experimentsmentioning
confidence: 99%
“…For L. minor, the lethal concentration of 50% (CL50;7d) of atrazine was 5.27 mg L (Cedergreen et al, 2007); to the atrazine, isoproturon and alachlor mixture (50+35+15%), with CL50;96h of 70.0 µg L -1 (Coutris et al, 2011); and than imazapyr, with CL50;7d of 1.06 mg L -1 (Cruz et al, 2015); however, it was more sensitive to glyphosate (CL50 of 19.6 mg L -1 ) and to mecoprop, with 12.2 mg L -1 (Cedergreen et al, 2007 , and epoxiconazole, of 1.14 mg L -1 ; therefore, these authors mention that the magnification factor of the toxicity corresponded to 13.6 times in relation to the individual toxicity of each compound; however, this effect was not characterized for toxicity on L. minor.…”
Section: Ecotoxicity For L Minormentioning
confidence: 99%